2014
DOI: 10.1002/ange.201403247
|View full text |Cite
|
Sign up to set email alerts
|

Redox Chemistry of a Hydroxyphenyl‐Substituted Borane

Abstract: Chemical reduction of a hydroxyphenyl-substituted borane triggers a sequential electron-and intramolecular hydrogen-atom-transfer process to afford a hydridoborate phenoxide dianion. On the other hand, hydrogen-atom abstraction of the borane leads to the isolation of a neutral borylated phenoxyl radical, which can be transformed to the corresponding benzoquinone borataalkene derivative by reduction with cobaltocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Heyduk and co-workers showed that bis­(3,5-di tert -butyl-2-phenol)­amine ([ONO]­H 3 ) complexes of aluminum­(III) perform electron-transfer reactions with a variety of quinones (Scheme B), while Graves and co-workers studied doubly reduced α-diimine ligand complexes of aluminum­(III) that promote one-electron transfer in the presence of oxidants like AgCl (Scheme C) . In boron chemistry, phenoxide ligands have been observed to undergo reduction to a phenoxyl radical …”
Section: Introductionmentioning
confidence: 99%
“…Heyduk and co-workers showed that bis­(3,5-di tert -butyl-2-phenol)­amine ([ONO]­H 3 ) complexes of aluminum­(III) perform electron-transfer reactions with a variety of quinones (Scheme B), while Graves and co-workers studied doubly reduced α-diimine ligand complexes of aluminum­(III) that promote one-electron transfer in the presence of oxidants like AgCl (Scheme C) . In boron chemistry, phenoxide ligands have been observed to undergo reduction to a phenoxyl radical …”
Section: Introductionmentioning
confidence: 99%
“…Peng’s research interests are in crystallography and inorganic chemistry, including the synthesis of molecular metal wires. He has reported in Chemistry—A European Journal on heteropentanuclear extended metal‐atom chains,2a and in Angewandte Chemie on the reduction of hydroxyphenyl‐substituted boranes 2b. Peng is on the International Advisory Board of the European Journal of Inorganic Chemistry…”
Section: Awarded …︁mentioning
confidence: 99%